2018
DOI: 10.1111/jcmm.14042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum exosomal LncRNA‐based biomarker panel for diagnosis and recurrence prediction of bladder cancer

Abstract: Exosomes are small membrane vesicles released by many cells. These vesicles can mediate cellular communications by transmitting active molecules including long non‐coding RNAs (lncRNAs). In this study, our aim was to identify a panel of lncRNAs in serum exosomes for the diagnosis and recurrence prediction of bladder cancer (BC). The expressions of 11 candidate lncRNAs in exosome were investigated in training set (n = 200) and an independent validation set (n = 320) via quantitative real‐time PCR. A three‐lncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 41 publications
0
106
0
Order By: Relevance
“…Studies have found that long noncoding RNAs (lncRNAs) can be expressed in exosomes derived from tumor serum, cells, and microenvironment . Studies have shown that serum and urine exosome lncRNA can be used as biomarkers for the diagnosis and prognosis of BC . In addition, exosomal lncRNA is also involved in the regulation of BC development .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that long noncoding RNAs (lncRNAs) can be expressed in exosomes derived from tumor serum, cells, and microenvironment . Studies have shown that serum and urine exosome lncRNA can be used as biomarkers for the diagnosis and prognosis of BC . In addition, exosomal lncRNA is also involved in the regulation of BC development .…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Hence, great attention is required for early diagnosis and prognosis prediction. 27 In addition, there is growing evidence that lncRNA might act as prognostic indicators in BLCA development and progression. 25,26 Nowadays, a set of studies elucidated that lncRNAs exerted a lot in the pathogenesis of BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…25 Similarly, Lee et al validated the importance of serum exosomal ncRNAs (miRNA-21 and lncRNA-ATB) in the diagnosis and prognosis monitoring of human HCC. qRT-PCR, reverse transcription quantitative real-time polymerase chain reaction group and the control group was 0.857 and 0.826.…”
Section: As1 Expression In Gcmentioning
confidence: 99%